Design of Hotel Warehouse Management Information System Based on PIECES Analysis - Risanti Iswardani, Putu; Surya Pramana, I Wayan; Prapto Sudarmodjo, Yanu (International Journal of Engineering and Emerging Technology; Vol 3 No 2 (2018): July - December, 2019)
The hotel warehouse section requires a good information system that can support all warehouse operational processes so that service quality, information accuracy and control of data security can be achieved in accordance with the company's objectives in the hotel warehouse. An information system is built from a design that is based on the needs of users of information systems and an analysis of the operational conditions of the company. Based on this, the purpose of this study is to analyze and design a management information system to be able to support the operational processes of the hotel warehouse. The case study in this study is the warehouse section at the Mercure Bali Nusa Dua Hotel. The system design is described through the stages in the Waterfall method and for the analysis of the system that has been running the PIECES method is used. The conclusion of this study is that users expect management information systems to be able to support processes that currently cannot be overcome using a system that has been running and system design has been made based on user expectations, with the hope that the output of the new system can meet user needs